2015
DOI: 10.3390/genes6020206
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Mutations in ABCC8 and KCNJ11 Genes in Saudi Persistent Hyperinsulinemic Hypoglycemia of Infancy (PHHI) Patients

Abstract: The autosomal recessive form of persistent hyperinsulinemic hypoglycemia of infancy (PHHI) is associated with mutations in either ABCC8 or KCNJ11 genes. In the present study, we describe the clinical features and results of genetic analysis of 13 Saudi Arabian patients with PHHI. Clinically, most patients presented with infantile seizures and/or developmental delay, with a subset of patients who were also found to have abnormal brain imaging and electrophysiological studies. Interestingly no coding pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Until diazoxide is proven to be safe, we do not recommend diazoxide as a treatment for pulmonary hypertension. While SUR1-dependent K ATP activation is an intriguing potential basis for pulmonary hypertension therapy, 32 ultimately, K ATP channel activators with less pulmonary toxicity may prove useful for pulmonary hypertension treatment. 33…”
Section: Discussionmentioning
confidence: 99%
“…Until diazoxide is proven to be safe, we do not recommend diazoxide as a treatment for pulmonary hypertension. While SUR1-dependent K ATP activation is an intriguing potential basis for pulmonary hypertension therapy, 32 ultimately, K ATP channel activators with less pulmonary toxicity may prove useful for pulmonary hypertension treatment. 33…”
Section: Discussionmentioning
confidence: 99%
“…In Arabian descent populations, four studies have been performed; one in Tunisia that showed high prevalence of c.1227-1228dup [ 30 ] , the second in Morocco that introduced three variants (c.494A>G, c.1145G>A, and c.1185_1186dup) [ 31 ] , the third in Saudi Arabia that revealed the presence of V22M, Y165C, H324Q, and G382D variants [ 32 ] , and the last in Egypt that found a significant association between G396D and Y179C mutations and colorectal carcinogenicity [ 33 ] . These results contradict with those obtained from a study involved 360 Arabic patients [ 34 ] .…”
Section: Discussionmentioning
confidence: 99%